Robot Pintar Penyambut Costumer pada Pusat Perbelanjaan Kota Manado - Muhamad Dwisnanto Putro; Jane Litouw (Jurnal Rekayasa Elektrika, 2017)
Aspects of robotics technology have now been able to explore and reach the entertainment, education, and health.  Making robots with privileges and special expertise is closely related to the needs of the modern world that requires a device with a high capacity are useful to help the work of man. On the other hand, advanced technology is useful to complete the work that could not and did not want to do by men as a greeter job. Greeter costumer jobs is a very tedious job. So it is necessary in the field of robotics technology that is smart robot greeter customers that replace the role of humans to improve the quality of waiters, efficiency, and economical savings at shopping centers in the city of Manado. The smart robot is designed to greet the customer by giving the greeting on the customer entrance and exit shopping center. The robot system is powered with less use of multiple technologies including ultrasonic distance and PIR sensors to detect humans, servo and DC motor as an actuator of the robot, and use voice module so that the robot can speak. The robot system is also equipped with a remote control using the Android smartphone so the smart robot can perform monitoring, operation, and control over long distances. The test results describe the action of robots have been able to make the detection of costumer and activities greeting the customer with the analysis of determining the value of the parameter distance between ultrasonic sensors use trigonometry comparative analysis.